PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI PEMODERASI - Sari, Fitriana Warap; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of ownership structure to the performance of the company with the capital structure as the moderatingon Chemical companies which are listed in Indonesia Stock Exchange during the 2011-2013 periods. The samples have been selected by using purposive sampling technique so 10 chemical companies (30 firm year) which meet the criteria have been selected as samples. The regression equation in this research is the Moderated Regressions Analysis (MRA) which is appliedto test whether the moderating variable can strengthen or weaken the correlation among the independent variables to the dependent variable. The analysis technique has been carried out by using multiple regressions with the support of SPSS 16 version program. Based on the result of multiple regressions analysis with the significance rates is 5%, therefore this research shows that: 1) the first hypothesis, the influence of correlation between ownership structure to the performance of the company can be accepted with its significance rates is 0.045 to positive direction, 2) the second hypothesis, the influence of the correlation between capital structure to the performance of the company can be accepted with its significance rates is 0.013 to positive direction, and 3) the third hypothesis, the moderatinginfluence of capital structure to the correlation between ownership structure to the perfrmance of the companycan be accepted with its significant rates is 0.051 to the positive direction. Therefore, the capital structure canpositively moderate the correlation between ownership structure to the performance of the company.Keywords: Ownership Structure, Company Performance, and Capital Structure of the Company